Pentahelix Strategy, Innovation Capacity, and MSME Competitive Strength in West Bangka Regency - Erwin Erwin; Amri Amri; Yulianti Yulianti; Burham Isnanto (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2026)
Fewer than 18% of the more than 2,500 micro, small, and medium enterprises (MSMEs) registered in West Bangka Regency sustain competitiveness in national markets, a condition attributed primarily to limited technology adaptation and constrained innovation capability. This study examines the influence of Government Role (X1), Business Role (X2), and Media Role (X3) within the Pentahelix strategy on MSME Competitive Strength (Y) through the mediation of Innovation Capacity (M). Using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0, data were collected from 345 MSME respondents in West Bangka Regency during January through March 2024. All seven hypotheses were supported. The highest path coefficient was observed on the Business Role to Innovation Capacity path (β = 0.507, t = 4.310, p < 0.001). Innovation Capacity partially mediated both the Business Role (indirect effect = 0.050, VAF = 38.5%) and Media Role (indirect effect = 0.039, VAF = 34.2%) relationships with Competitive Strength. Government Role produced a stronger direct effect on Competitive Strength (β = 0.218) than on Innovation Capacity (β = 0.082). This study contributes a more focused mediation model than prior Pentahelix research by retaining only three empirically supported stakeholder elements as simultaneous predictors of Innovation Capacity, producing a parsimonious and policy-relevant model for the archipelago MSME context.